Novel therapeutic strategies targeting resistance mechanisms in hematologic malignancies: from BCL2 inhibition to immunomodulatory approaches - Han, Qianyu; Jiang, Shasha; Chen, Jirui; Xue, Lei (Frontiers in Pharmacology, 2026)
BackgroundHematologic malignancies, including chronic lymphocytic leukemia (CLL), acute myeloid leukemia (AML), non-Hodgkin lymphoma (NHL), and multiple myeloma (MM), are characterized by high relapse rates due to intrinsic and acquired drug resistance. Resistance mechanisms often involve dysregulation of apoptosis pathways, such as B-cell lymphoma 2 (BCL2) family overexpression, and immune evasion through microenvironment modulation.PurposeThis review synthesizes recent advances (2020–2025) in therapeutic strategies targeting these mechanisms, focusing on BCL2 inhibition and immunomodulatory approaches to overcome resistance and improve outcomes.MethodsWe systematically reviewed literature from PubMed, Nature, and other databases, emphasizing clinical trials, mechanistic studies, and emerging combinations published between 2020 and 2025. Main Findings: BCL2 inhibitors like venetoclax have achieved high response rates (ORR >70%) in CLL and AML but face resistance via MCL1/BCL-XL upregulation. Next-generation agents (e.g., sonrotoclax) and combinations address this. Immunomodulatory therapies, including immunomodulatory imide drugs (IMiDs) and chimeric antigen receptor T-Cell immunotherapy (CAR-T cells), enhance T/NK cell activity, with objective response rate (ORR) up to 90% in relapsed MM. Integrated strategies combining BCL2 inhibition with immunotherapy show synergistic effects, improving progression-free survival (PFS) by 30%–40%.ConclusionThese strategies represent a paradigm shift toward precision medicine, but challenges like toxicity and biomarker-driven resistance persist. Future directions include AI-guided predictions and novel degraders like proteolysis-targeting chimeras (PROTACs).